2015
DOI: 10.1080/09585192.2015.1075574
|View full text |Cite
|
Sign up to set email alerts
|

Work–family enrichment and satisfaction: the mediating role of self-efficacy and work–life balance

Abstract: Although the direct effects of work-family enrichment on satisfaction are well-documented, previous theoretical predictions and empirical findings of the relationship have been inconsistent. Drawing on social cognitive theory, the current research examined how workfamily enrichment contributes to job and family satisfaction by exploring the mediating mechanisms of self-efficacy and work-life balance. This study also empirically validated a new self-efficacy measure using the work-life interface nomological net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 82 publications
10
108
0
7
Order By: Relevance
“…For example, those high in self-efficacy can work efficiently, therefore saving resources for other purposes such as life outside of work (Judge & Bono, 2001). Thus, we believe that developing this psychological resource through work may enhance the experience of WFE as previous work has demonstrated a positive relationship between self-efficacy and WFE (Chan et al, 2016).…”
Section: Work Resourcesmentioning
confidence: 99%
“…For example, those high in self-efficacy can work efficiently, therefore saving resources for other purposes such as life outside of work (Judge & Bono, 2001). Thus, we believe that developing this psychological resource through work may enhance the experience of WFE as previous work has demonstrated a positive relationship between self-efficacy and WFE (Chan et al, 2016).…”
Section: Work Resourcesmentioning
confidence: 99%
“…In fact, there are studies that indicate that WLB programs show indirect effects to help employees improve their well-being conditioned by individuals' positive attitudes and their life coping strategies [50]. For instance, the WLB has been demonstrated to have positive relation to the employee self-efficacy [31]. Other study shows that the emotionally intelligent employees are better in managing their WLB and are more satisfied with their job [24].…”
Section: Work-life Balance For Fulfilling the Needs Of New Generationsmentioning
confidence: 99%
“…Moving to a rich WLB, literature indicates that WLB helps in the development of psychological availability and augmenting employee positive energy [30], and highlights that the satisfaction level with the WLB plays a role in supporting mental health [22]. Others works have indicated that WLB has a positive effect on job and family satisfaction [31], and recently it has been proved that a positive correlation exists between job satisfaction and WLB [24].…”
Section: Introductionmentioning
confidence: 99%
“…WFB, defined as the ‘accomplishment of role‐related expectations that are negotiated and shared between an individual and his/her role‐related partners in the work and family domains’ (Carlson, Grzywacz and Zivnuska , 1459), has been shown to positively relate to job and family satisfaction (Chan et al. ) and negatively relate to anxiety and depression, across cultures (Haar et al. ).…”
mentioning
confidence: 99%